Risk Management Practices and Financial Performance of Property Developers in the Context of Covid-19 Pandemic - Lau, Kah Yee; Tey, Jia Hong; Ting, Irene Wei Kiong (GBMR, 2023)
The global economy can be impacted by significant events such as financial crises and pandemics. Recently, the outbreak of COVID-19 caused by the SARS-CoV-2 virus has disrupted the stability of markets and economies across various sectors. One area of interest is the risk management practices of property developers and their impact on financial performance during the pandemic. This study aims to investigate the risk management practices of property companies in Malaysia in the context of the COVID-19 pandemic. Specifically, the five areas being explored are identifying risks, assessing risks, mitigating risks, implementing risk management, and monitoring risk management. The research seeks to provide theoretical contributions by offering insights to organizations on how to improve their financial performance, as well as practical contributions by providing guidelines for more structured risk management practices. The study employs a quantitative research approach, with a random sampling of 282 respondents from various property developers in Malaysia, including residential, commercial, mixed-use, special purpose, industrial, and agricultural sectors. Results indicate that risk mitigation has a significant positive effect on financial performance, while risk identification and risk assessment have negative effects.